المهارات الميلتونية والقراءة التأويلية الجديدة - كريم, ظاهر لطيف; علي, ژینۆ عبدالله (Sulaimani Journal for Humanities, 2021)
This study ،entitled Milton،s Skills – New Interpretation reading-،Nazik Al-Malaika as an example ،comprises the depth of psychology and interpretation analysis of an American scholar Milton Ericksons ( 1901- 1980 ) theory or skills which give power and true meaning to our words، in particular ،the inner meanings of the words and sentences ،or it speaks for us when we aren’t saying anything at all. The theory of Milton Erickson ،the father of hypnotic ،came to us in order to know what happens inside the unconscious world.This call it the system of provide and operation of unconscious .The main skills depend of the followings: hypothesis، reading minds، the fact of desire and possibility ،reasons and effects ،hidden contexts ،borrowing ،finally ،binary assumptions .In these skills ، the most importance language for learning is method of meta-language which can go to a deep structure of the unknown minds ،because Milton Erickson believed that the language of unconscious is a type of imagination and metaphor ،and therapeutic stories ،anecdotes ،jokes. In Erickson hypnosis، language is used to direct attentions inwards on a search for learning and meaning.